2021
DOI: 10.1186/s13756-021-01006-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of topical vancomycin in the prevention of spinal surgical site infections: a retrospective cohort study

Abstract: Background The risk of surgical site infections (SSIs), particularly methicillin-resistant Staphylococcus aureus (MRSA) SSIs, after spinal surgeries is one of the most daunting experiences to patients and surgeons. Some authors suggest applying vancomycin powder on the wound before skin closure to minimize the risk of SSIs; however, this practice is not supported by well-established evidence. This study sought to assess the effectiveness of topical (i.e. intra-wound) vancomycin in minimizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 62 publications
0
12
0
Order By: Relevance
“…A total of 2367 relevant studies were screened, of which 42 studies between 2011 and 2022, met the inclusion criteria and were involved in the meta‐analysis. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Data obtained from these studies were shown in Table 2 . The selected studies included 24 137 subjects with neurosurgery at the baseline of the studies; 10 496 of them were using the powdered vancomycin, and 13 641 were not using the powdered vancomycin as a control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 2367 relevant studies were screened, of which 42 studies between 2011 and 2022, met the inclusion criteria and were involved in the meta‐analysis. 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Data obtained from these studies were shown in Table 2 . The selected studies included 24 137 subjects with neurosurgery at the baseline of the studies; 10 496 of them were using the powdered vancomycin, and 13 641 were not using the powdered vancomycin as a control.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 2367 relevant studies were screened, of which 42 studies between 2011 and 2022, met the inclusion criteria and were involved in the meta‐analysis 22‐63 . Data obtained from these studies were shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 While some studies have found topical vancomycin effective in preventing SSI after spine surgery, others have not found a significant decrease in SSIs with topical vancomycin in pediatric patients undergoing spine surgery. [19][20][21][22] Given that BPGs were published in September 2019, perhaps it is too early for consensus guidelines to have made a substantial impact on reducing variability in SSI prevention and prophylactic antibiotic use. Guidelines may impact patients on an institutional level not captured in the present study.…”
Section: Discussionmentioning
confidence: 99%